Counting sleep? Critical reflections on a UK national sleep strategy. Issue 4 (8th August 2021) - Meadows, Robert; Nettleton, Sarah; Hine, Christine; Ellis, Jason
ABSTRACT: The United Kingdom Government are planning to issue guidance on sleep duration. Whilst sleep is clearly important for health, offering such guidance is not the answer. Within this commentary we put forward three arguments to support this claim: (i) sleep is liminal and beyond the limits of voluntary agency; (ii) sleep is linked to structural inequality; and (iii) sleep is multiple. The first two points are now well established. However, the third encourages a considerable break from established thinking. Recent research has highlighted that we need to move away from viewing sleep as a singular, objectively defined phenomenon, and instead position it as many different practices woven together. Sleep is situated, contingent and is enacted in multiple ways. Public health would be better served by a ground-up approach which explores good and poor sleep across these three axes: liminality, social position, and ontology.